Analisis Kesalahan Ejaan Bahasa Indonesia pada Abstrak Skripsi Mahasiswa Fakultas Teknik Universitas Madura - Balya Firjawun Sabila; Laili Amalia; Ria Kasanova (Pusat riset dan Inovasi Nasional, 2026)
This study aims to describe spelling errors found in undergraduate thesis abstracts written by students of the Faculty of Engineering, Universitas Madura, based on the provisions of the Fifth Edition of Indonesian Spelling Guidelines (Ejaan Bahasa Indonesia/EBI). The study employed a qualitative descriptive design. The data consisted of thesis abstracts collected from the Universitas Madura Library. Data were gathered through documentation and text observation and analyzed through identification, classification, tabulation, and interpretation stages. The findings revealed 118 spelling errors, consisting of 47 letter usage errors (39.8%), 41 word-writing errors (34.7%), and 30 punctuation errors (25.5%). Letter-related errors were predominantly associated with inappropriate capitalization, while word-writing errors were dominated by non-standard word forms and incorrect affixation. Punctuation errors mainly involved the misuse of commas. These findings indicate that the implementation of Indonesian spelling conventions in thesis abstracts remains suboptimal. The errors reflect not only insufficient mastery of spelling rules but also limited academic editing practices among students. This study provides empirical evidence regarding the quality of spelling usage in academic writing among engineering students and offers a basis for strengthening academic literacy and scientific writing instruction in higher education.